The Influence of Artificial Intelligence, Audit Information System, and Remote Audit on Auditor Performance - Fidel Muhammad Purwadi; Murtanto Murtanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of Artificial Intelligence, Audit Information Systems, and Remote Audits on Auditor Performance by adopting the Theory of Planned Behavior and the Technology Acceptance Model. The research uses primary data obtained through questionnaires distributed to auditors who hold a bachelor's degree, work at Public Accounting Firms (KAP), and have knowledge of Artificial Intelligence, Audit Information Systems, and Remote Audits. The sampling technique employed is purposive sampling. The results show that all three independent variables have a positive and significant influence on auditor performance. Artificial Intelligence has been proven to enhance the efficiency and effectiveness of auditors’ work. Audit Information Systems support a more structured and accurate audit process, while the implementation of Remote Audits provides greater flexibility and accessibility in audit execution. These findings indicate that the optimal use of digital technology can significantly improve overall auditor performance.